Mehrdimensionale Lieferantenbewertung - Falzmann, Juliane; Justus Liebig University Giessen (My University, 2007)
Die Arbeit beschäftigt sich mit dem in der Literatur noch unzureichend dokumentierten Thema der Wertschöpfungsketten-Betrachtung bezogen auf das Lieferantenmanagement - insbesondere der Lieferantenbewertung. Um diese Lücke zu schließen, werden die einzelnen Schritte einer Lieferantenbewertung explizit heraus gearbeitet. Beginnend bei der Identifikation potenzieller Lieferanten und deren Eingrenzung, erfolgen eine Analyse und eine Bewertung der Lieferanten, um auf deren Basis schließlich den oder die besten Lieferanten auszuwählen, stetig zu kontrollieren und die Lieferanten-Abnehmer-Beziehung zu steuern. Der Prozessgedanke kommt nicht zuletzt dadurch zum Ausdruck, dass der Status Quo des Lieferantenmanagements niemals als Endpunkt angesehen werden darf, vielmehr ist eine permanente Überwachung und Optimierung des eigenen Lieferantenstamms erforderlich. Diese wird durch die unterschiedlichen Herangehensweisen in Bezug auf neue und bereits vorhandene Lieferanten unterstützt und bekräftigt. Die Lernprozesse, welchen sowohl die Lieferanten als auch die Abnehmer unterliegen, werden auf diese Weise anschaulich dargestellt. Indem die Arbeit jeden Prozessschritt der Lieferantenbewertung verfolgt und auf die einzelnen Schritte von der Identifizierung der Lieferanten über die Bewertung jedes Lieferanten bis zu individuellen Schlussfolgerungen detailliert eingeht, wird nicht nur der gesamte Prozess verfolgt, es werden auch Hinweise und Ergebnisse aus den einzelnen Schritten aufgezeigt und erläutert. Diese bisher für den Lebensmittelhandel noch nicht durchgeführte Lieferantenbewertung liefert einen wichtigen Baustein im komplexen System des Lieferantenmanagement für den Sektor des Lebensmittelhandels.

The paper points towards the fact that the specific relationship between a supplier and customer is largely determined on the basis of the following: the annually negotiated terms and conditions, turnover and gross profits. A comprehensive and multidimensional supplier assessment does not normally take place, even though companies today maintain relationships beyond the buyer and supplier level, with manufacturers, quality-management, sales organisation, logistics, customer service, etc. The underlying objective of this paper is to identify possible solutions to satisfy both practical and academic criteria, pointing to both potential improvements for both supplier and buyer, thereby enhancing their mutual economic relationship. A review of the development from buying to supply chain management leads to strategic supplier management and consequently to the process of supplier assessment, which is regarded a component of supplier management. The detailed explanation of the three basic elements of supplier management: supplier selection, assessment and development, clarifies the relation between theseterms and allows a categorisation into the area of supplier controlling. Special attention is given to the instruments used in the supplier appraisal process, dividing them into three categories. The first category includes simple tools such as interviews and inspections. The second category covers established instruments such as ABC and Portfolio-Analysis. Modern instruments, e.g. Balanced Scorecard and Evaluation Matrix, are sorted into a third category. The explanation of modern instruments bridges the gap to part B of this paper, exemplified with a supplier assessment questionnaire, followed by presentation of the result in a portfolio matrix. The first step consists in collecting questions for the multidimensional supplier assessment and then sorting these into previously established subject categories. Recommendations were followed from literature whilst also integrating suggestions provided by the retailers responsible senior managers. Six main subject categories were identified: quality of service, quality, innovation, capacity to cooperate, stakeholders and discount chains. The questions were sorted into the identified categories and weighted; followed by a weighting of the categories themselves. In this particular case the weighting was carried out by three retailers managing directors. The relative weighting can vary according to industry in question and products examined, demonstrating the importance of the individual categories and evaluation criteria. A supplier criterion is allocated a high weighting if considered important for the supplier selection process. The sum adds up to 100, both on the level of categories and sub-categories (to 1 respectively when using another scale). Following the weighting a trial was completed with ten selected suppliers of a single product category. The questionnaires were sent to both the suppliers and retailer. 9 out of 10 suppliers replied within 93 days, showing that the number of questions answered decreased with the duration required to respond. To give an example, supplier 10 had not answered 16 of the 68 questions within 93 days. These unanswered questions were attributed the score of zero for the assessment. After evaluating the responses using MS Excel tables, it was possible to identify two distinct categories of suppliers. Four suppliers scored a result of 76% or more and another four suppliers scored less than 60%. One additional supplier scored 67% positioning him in-between the identified categories. An explanation for the wide spread of results is to be found in the number of unanswered questions. In a second step these results are presented in a portfolio matrix. In this case the results are shown together with the suppliers gross profit. This method allows the suppliers to be placed into one of the four quadrants: 'don't promote'; accept; promote without advertising; promote with advertising . An immediate comparison of the suppliers under consideration is possible using this portfolio matrix. To ensure the practicability of the evaluation process a database is being built up. This will allow an initial indication for a feasible implementation of an assessment of 8,000 suppliers. The given example of feasibility should be seen as a guideline: it shows what an implementation could look like.
Keywords: Lieferantenrating; Handelslogistik; Lieferantenbewertung; Supply Chain Management; ddc:650